Future trends in optical wireless communications systems: Review - Jihad, Noor J; Abd Almuhsan, Murooj A (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Optical fibers are frequently used in data transmission systems, Because of their ability to transmit large amounts of information and dielectric nature. In central, metropolitan, or broad-area applications, network topologies incorporating many wavelengths per optical fiber are utilized to connect thousands of users with a wide variety of transmission rates and capacities. The simultaneous transmission of many wavelengths over a fiber with a nm range of 1300 to 1600 is a potent characteristic of an Optical communication network. Wavelength division multiplexing (WDM) is a method for combining various wavelengths onto a single fiber. The WDM concept, when combined with optical amplifiers, produces communication lines that enable quick communication between users across national borders. An overview of the difficulties with fiber-optic communication is provided in this paper. The areas that will be most important for the development of optical communications in the future are outlined in this study. Modern optical fibers and integrated optics were both developed in the dominion of optical machinery and parts. Optical fiber communication systems are widely used for high-speed data transmission over long distances. There are some specific details and examples of optical fiber communication systems such as Fiber Optic Cables, Light Sources, optical modulator, optical amplifier, optical receivers, fiber optical network, medical applications.